EU Medical Device Regulation – The Level of Convergence and Impact on Regulatory Complexity - Gavrilović Jankovič, Nika; Nikolić, Bruno (Review of European and Comparative Law, 2024)
Medical Device Regulation (MDR) entered into force in 2017 and became applicable in 2021. In the context of Europeanization and the European Union (EU) multilevel governance system, regulations are used as a means of unification. EU has gradually increased the degree of convergence in medical devices, even though medical devices pertain to the health sector, which is within the Member States’ competence. Despite MDR being a regulation, its preamble states that its aim is to harmonize rules for the placing on the market and use of medical devices on the EU market. This article analyzes the level of convergence introduced by the MDR and its impact on regulatory complexity. Our findings demonstrate that many relevant elements, such as mandatory CE marking, reached the level of unification, whereas some that are still to become legally effective, such as the European database on medical devices (EUDAMED), went further and reached the highest level – supranational and integral joint administrative capacities. Unlike the expected inverse correlation between EU convergence and regulatory complexity, our findings revealed that due to delays in bringing into effect certain unifying elements, de facto, MDR introduced additional constraints compared to the previous Medical Device Directive (MDD) framework. This leads to the main finding of this research, which is that the MDR convergence increase has led to a conflicting outcome – an increase in regulatory complexity.